Metabolic Syndrome Among Children and Adolescents Aged 10–18 Years - Martha Rodríguez-Morán; Beatriz Salazar-Vázquez; Rafael Violante; Fernando Guerrero‐Romero (2004)
Current definitions for the diagnosis of the metabolic syndrome are focused on adult populations (1–4), whereas specific criteria for its early diagnosis have never been formally defined for children and adolescents. Because the best approach for the prevention of the metabolic syndrome is early recognition, defining it in children and adolescents is necessary for estimating the magnitude of this health problem in the young population. In this study, we determine the prevalence of the metabolic syndrome among children and adolescents aged 10–18 years from northern Mexico and evaluate a definition for its early diagnosis in the young population.